How Early is Infants' Attention to Objects and Actions Shaped by Culture? New Evidence from 24-Month-Olds Raised in the US and China - Waxman, Sandra R.; Fu, Xiaolan; Ferguson, Brock; Geraghty, Kathleen; Leddon, Erin; Liang, Jing; Zhao, Min-Fang (Frontiers in Psychology, 2016)
Researchers have proposed that the culture in which we are raised shapes the way that we attend to the objects and events that surround us. What remains unclear, however, is how early any such culturally-inflected differences emerge in development. Here, we address this issue directly, asking how 24-month-old infants from the US and China deploy their attention to objects and actions in dynamic scenes. By analyzing infants’ eye movements while they observed dynamic scenes, the current experiment revealed striking convergences, overall, in infants’ patterns of visual attention in the two communities, but also pinpointed a brief period during which their attention reliably diverged. This divergence, though modest, suggested that infants from the US devoted relatively more attention to the objects and those from China devoted relatively more attention to the actions in which they were engaged. This provides the earliest evidence for strong overlap in infants’ attention to objects and events in dynamic scenes, but also raises the possibility that by 24 months, infants’ attention may also be shaped subtly by the culturally-inflected attentional proclivities characteristic of adults in their cultural communities.